2018
DOI: 10.18196/jmmr.7156
|View full text |Cite
|
Sign up to set email alerts
|

Disaster Risk Reduction and Emergency Preparedness for Children With Autism in Facing Earthquake Disaster in Yogyakarta

Abstract: Special Needs Children (ABK) is one of the vulnerable groups in times of disaster. Some of them have mobility hindrance even to perform a defence and personal escape independently, therefore, information is needed on what procedures or plans to take to rescue ABKs who need help from people around them (e.g. teachers, classmates, school staffs). Objectives: To determine the preparedness of children with special needs in dealing with earthquake disasters in Yogyakarta. This research uses a quasi-experiment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…With the numerous disasters worldwide of terrorist attacks, tsunamis, hurricanes, bombings, and earthquakes, the lack of focus on their psychological implications for children with ASD started coming to attention (2). Yet, beyond one study showing individuals with ASD to have decreased adaptive behaviors after exposure to an earthquake, and another indicating disaster awareness training to increase disaster preparedness of children with ASD, there is no data on how individuals with ASD react to disasters in general (3,4). Additionally, beyond any previous disasters, there is no information on how individuals with ASD are affected by pandemics.…”
Section: Introductionmentioning
confidence: 99%
“…With the numerous disasters worldwide of terrorist attacks, tsunamis, hurricanes, bombings, and earthquakes, the lack of focus on their psychological implications for children with ASD started coming to attention (2). Yet, beyond one study showing individuals with ASD to have decreased adaptive behaviors after exposure to an earthquake, and another indicating disaster awareness training to increase disaster preparedness of children with ASD, there is no data on how individuals with ASD react to disasters in general (3,4). Additionally, beyond any previous disasters, there is no information on how individuals with ASD are affected by pandemics.…”
Section: Introductionmentioning
confidence: 99%
“…Their awareness of potential risks can help reduce the negative impacts of natural disasters. The importance of disaster awareness is not only limited to theoretical knowledge but also involves real attitudes and actions (Nur Indriasari et al, 2018). Students in coastal and mountainous areas must be involved in disaster simulations, evacuation drills, and the formation of school emergency response teams (Shapira et al, 2018).…”
Section: Learning Outcomesmentioning
confidence: 99%
“…With the numerous disasters around the world, such as terrorist attacks, tsunamis, hurricanes, bombings, and earthquakes, a lack of focus on the psychological implications for children with ASD became apparent (Edmonds, 2017). However, aside from one study that found individuals with ASD to have decreased adaptive behaviors after being exposed to an earthquake, and another that found disaster awareness training to increase disaster preparedness in children with ASD, there is no data on how people with ASD react to disasters in general (Indriasari and Widyarani, 2018). Furthermore, aside from previous disasters, there is no information on how people with ASD are affected by pandemics.…”
Section: Introductionmentioning
confidence: 99%